The Analysis and Prediction of Land Use Changes Using Multi-Temporal Satellite Data in Shandiz City (Between 2000-2015) - foroozan taheri; Mohamad Rahim Rahnama; Omid Ali Kharazmi; Baratali Khakpoor (جغرافیا و توسعه, 2018)
In recent decades, rapid changes in land use and land cover in the touristic city of Shandiz, located at west of Mashhad Metropolis, has been accompanied with important consequences such as the destruction of natural resources, environmental pollution and improper growth of the city . The purpose of this investigation is the analysis and prediction of land use changes using multi-temporal satellite data for Shandiz (between 1379-1394). In this study, land cover changes in gardens and farms and constructed zones, wastelands and pastures land uses has been investigated using Landsat satellite imagery during the timeline between 1379 -1394 with the use of maximum likelihood algorithm, supervised method and Markov chain model. In Markov chain model, cover classes are used as pawns or chain status (transfer area matrix representing the number of pixels that converts from one class to other classes) or the area that has been changed from any use to other uses between 1379-1394. According to Markov CA model, area prediction for 4 land cover categories of land in the mentioned land uses were determined for the 1400 horizon. Depending on output data, it was found that during years 1379, 1388 and 1394, areas of constructed zones and wastelands land uses has increased greatly and whereas that of gardens, farms and pastures has decreased. Land use areas in the same in 1400 horizon in comparison to 1394. Areas of gardens and agriculture lands (%63), constructed zones (%126), wastelands (%97) and pastures (%96) will change accordingly.